2019
DOI: 10.1186/s13019-019-0888-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for the development of postoperative severe hypoxemia in obese women with acute type a aortic dissection

Abstract: Background The purpose of this study is to identify the risk factors for postoperative severe hypoxemia after surgery for acute type A aortic dissection. Methods This was a single-center retrospective study including 112 consecutive patients undergoing urgent aortic arch surgery for acute type A aortic dissection between December 2016 and April 2017 at Beijing Anzhen Hospital. Results Multivariate logistic regression analysis identified femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 23 publications
4
34
2
Order By: Relevance
“…We reasoned that since most of our patients transported from other hospitals takes a long time from symptom onset to entering the operating room, which would put the patients at a higher risk to develop the postoperative hypoxemia. Herein, we illustrated that higher BMI was linked to developing postoperative hypoxemia and severe hypoxemia in line with previous studies (8)(9)(10)(11)(12). Obesity, defined as BMI >25 kg/m 2 , had significant adverse effects on cardiopulmonary physiology.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We reasoned that since most of our patients transported from other hospitals takes a long time from symptom onset to entering the operating room, which would put the patients at a higher risk to develop the postoperative hypoxemia. Herein, we illustrated that higher BMI was linked to developing postoperative hypoxemia and severe hypoxemia in line with previous studies (8)(9)(10)(11)(12). Obesity, defined as BMI >25 kg/m 2 , had significant adverse effects on cardiopulmonary physiology.…”
Section: Discussionsupporting
confidence: 86%
“…Our study illustrated that the incidence of such complication was 84% (63/75), much higher than previous studies (30-50%) (6-11). However, the incidence of severe hypoxemia (P/F <100 mmHg) was 32% (24/75) in our study, slightly lower than a recent study (36.6%) (12). We reasoned that since most of our patients transported from other hospitals takes a long time from symptom onset to entering the operating room, which would put the patients at a higher risk to develop the postoperative hypoxemia.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous studies, as well as the present study, have shown CPB time to be significantly prolonged among obese compared with non-obese patients. 14 16 Cooling and rewarming tend to be prolonged in obese patients. We recently reported that double arterial cannulation yielded acceptable outcomes and seems effective for the prevention and management of intraoperative malperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Of 64 studies reporting outcomes of patients included in this report 13–76 . The proportions of studies from Asia, Europe, and North America were 54.7%, 31.3%, and 10.9%, respectively.…”
Section: Methodsmentioning
confidence: 99%